2008
DOI: 10.1177/089686080802800108
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Bicarbonate/Lactate and Standard Lactate Dialysis Solution in Peritoneal Transport and Ultrafiltration: A Prospective, Crossover Single-Dwell Study

Abstract: Objective It has been proposed that biocompatible bicarbonate/lactate based (Bic/Lac), physiologic-pH peritoneal dialysis (PD) solutions will be beneficial in long-term PD. However, we do not yet have detailed knowledge concerning the comparative physiology of buffer transport for these new solutions and their impact on underlying peritoneal transport of solutes and ultrafiltration (UF). The purpose of this study was to investigate the profile of buffer handling and peritoneal membrane transport characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 24 publications
2
32
1
Order By: Relevance
“…Both show a decrease after 3 to 4 years. The developments in small solute transport are likely caused by neoangiogenesis (20,36), leading to an enlarged peritoneal vascular surface area (37). Besides cytotoxic effects of GDPs on the mesothelial cell layer (31,(38)(39)(40)(41), a more likely explanation is their promotion of the formation of advanced glycosylation end products (AGEs) that accumulate in the peritoneal vascular wall and induce neoangiogenesis (32,33).…”
Section: The Interaction Between the Dialysis Solution Peritonitis Amentioning
confidence: 99%
“…Both show a decrease after 3 to 4 years. The developments in small solute transport are likely caused by neoangiogenesis (20,36), leading to an enlarged peritoneal vascular surface area (37). Besides cytotoxic effects of GDPs on the mesothelial cell layer (31,(38)(39)(40)(41), a more likely explanation is their promotion of the formation of advanced glycosylation end products (AGEs) that accumulate in the peritoneal vascular wall and induce neoangiogenesis (32,33).…”
Section: The Interaction Between the Dialysis Solution Peritonitis Amentioning
confidence: 99%
“…It has been suggested that vasoactive substances may influence blood flow or the permeability of the peritoneal vascular bed (9,19,20). Fang et al (11) reported that, compared with a high-GDP exchange, a single exchange of low-GDP solution (Physioneal: Baxter Healthcare Corporation, Deerfield, IL, USA) resulted in a lower UFV and similar solute transport during a 2.5% glucose PET. Kim et al (18) reported that an increased D/P Cr (and consequently, a lower UFV) in a low-GDP group (Stay • Safe Balance) might provide a lower risk of intravascular volume depletion and a higher probability of RRF preservation.…”
Section: Discussionmentioning
confidence: 99%
“…Venous blood samples drawn at 0, 120, and 240 minutes were assayed for glucose, urea, and creatinine. Creatinine measurements were corrected for the presence of glucose (11).…”
Section: Petmentioning
confidence: 99%
See 2 more Smart Citations